Risk Management and Assessment 2020
DOI: 10.5772/intechopen.91463
|View full text |Cite
|
Sign up to set email alerts
|

Risk Management in Biobanks

Abstract: The administration of risks is usually an important corner stone of professional operations. Nevertheless, specifically for biobanking organizations, risk recognition, control, management, and easing are inevitably extremely critical elements of everyday operations. The costly kind of unique samples/cell lines, data and also other high-pitched value biobanking products and services such as cell-based drugs, and biologically active pharmaceutical materials call for tremendously precise planning-including the fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Using the SWOT analysis as a risk management tool, Sargsyan et al have determined the strengths, weaknesses, opportunities and threats of two emerging Biobanks at the National Institute of Public Health of Kosovo and the University of Tirana Medicine. On the basis of this analysis, they then defined more efficient strategies for biobanking processes and the use of existing infrastructures and knowledge in research [ 19 ]. Miranda et al summarize the potential risks and control measures associated with the acquisition of human samples in research identified in projects under the remit of the UCL/UCLH Biobank for Studying Health and Disease of University College London Cancer Institute at London, as well as transportation, use, storage and disposal of human samples and the security of the premises [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using the SWOT analysis as a risk management tool, Sargsyan et al have determined the strengths, weaknesses, opportunities and threats of two emerging Biobanks at the National Institute of Public Health of Kosovo and the University of Tirana Medicine. On the basis of this analysis, they then defined more efficient strategies for biobanking processes and the use of existing infrastructures and knowledge in research [ 19 ]. Miranda et al summarize the potential risks and control measures associated with the acquisition of human samples in research identified in projects under the remit of the UCL/UCLH Biobank for Studying Health and Disease of University College London Cancer Institute at London, as well as transportation, use, storage and disposal of human samples and the security of the premises [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Risk governance is entangled with “design and role, organizational capacity, stakeholder involvement, collaborative decision making and political accountability” as well as responsibility at the institutional level while it necessitates the involvement of various stakeholders “for the development and use of scientific knowledge within the risk governance process” ( Renn and Walker, 2008 ). Risk assessment that includes risk mapping/identification and evaluation is by nature a highly critical component for biobanking organizations ( Sargsyan et al, 2020 ) and should be a regular practice in order to strengthen precautions and create contingency plans that must be in place for unexpected events that will affect biobanking operations ( Eng and Tan, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Менеджмент рисков в последние годы стал одним из ключевых аспектов организации и управления работой биобанков и представляет собой часть общей системы управления, направленной на преждевременное выявление, анализ и минимизацию событий, реализация которых способна повлечь за собой негативные последствия для биобанка, а также повлиять на качество биообразцов и ассоциированных с ними данных [1,2].…”
Section: Introductionunclassified